Nanopore sequencing and hybrid assembly: unraveling the genomic landscape of dollar spot with enhanced annotation and drug resistance profiling - Xiaojing Shi; Shu Zhao; John G. Gibbons; Geunhwa Jung (Frontiers in Fungal Biology, 2025)
The increasing multi-drug resistance observed in the turfgrass pathogen Clarireedia spp. has emerged as a critical issue. Understanding the mechanisms underlying fungicide resistance is crucial to address this challenge. This study focuses on comparing a highly propiconazole-resistant isolate of Clarireedia jacksonii, HRI11, with a sensitive isolate, HRS10. Genomes were sequenced using the Oxford Nanopore MinION sequencing platform, and hybrid assembly was performed using this data and existing Pacific Biosciences long reads and Illumina short reads. HRI11 genome assembly represents the most contiguous and complete genome assembly reported for Clarireedia to date, spanning 43.6 MB with 12,831 predicted protein-coding genes across 51 scaffolds. In contrast, the HRS10 had an assembly size of 39.6 MB and encoded 12,161 putative proteins distributed over 100 scaffolds. While the two isolates share substantial sequence similarity and overall protein content, the fungicide resistance observed in HRI11 appears to arise primarily from genetic variants, particularly in genes encoding transcription factors, transporters, and fungicide target genes. These genetic variants establish a foundational resistance level against fungicides. Furthermore, induced resistance in HRI11 involves increased expression of proteins that facilitate fungicide efflux, thereby optimizing energy allocation during fungicide exposures. Together, these mechanisms-inherent genetic variation and adaptive transcriptional responses-contribute to the heightened resilience of HRI11 under fungicide treatment.